Abnormal Whisker-Dependent Behaviors and Altered Cortico-Hippocampal Connectivity in Shank3b−/− Mice. (18th November 2021) - Balasco, Luigi; Pagani, Marco; Pangrazzi, Luca; Chelini, Gabriele; Ciancone Chama, Alessandra Georgette; Shlosman, Evgenia; Mattioni, Lorenzo; Galbusera, Alberto; Iurilli, Giuliano; Provenzano, Giovanni; Gozzi, Alessandro; Bozzi, Yuri
Abstract: Abnormal tactile response is an integral feature of Autism Spectrum Disorders (ASDs), and hypo-responsiveness to tactile stimuli is often associated with the severity of ASDs core symptoms. Patients with Phelan-McDermid syndrome (PMS), caused by mutations in the SHANK3 gene, show ASD-like symptoms associated with aberrant tactile responses. The neural underpinnings of these abnormalities are still poorly understood. Here we investigated, in Shank3b −/− adult mice, the neural substrates of whisker-guided behaviors, a key component of rodents' interaction with the surrounding environment. We assessed whisker-dependent behaviors in Shank3b −/− adult mice and age-matched controls, using the textured novel object recognition (tNORT) and whisker nuisance (WN) test. Shank3b −/− mice showed deficits in whisker-dependent texture discrimination in tNORT and behavioral hypo-responsiveness to repetitive whisker stimulation in WN. Sensory hypo-responsiveness was accompanied by a significantly reduced activation of the primary somatosensory cortex (S1) and hippocampus, as measured by c- fos mRNA induction, a proxy of neuronal activity following whisker stimulation. Moreover, resting-state fMRI showed a significantly reduced S1-hippocampal connectivity in Shank3b mutants, in the absence of altered connectivity between S1 and other somatosensory areas. Impaired crosstalk between hippocampus and S1 might underlie Shank3b −/− hypo-reactivity to whisker-dependent cues, highlighting a potentially generalizable somatosensory dysfunction in ASD.